The σB-dependent regulatory sRNA Rli47 represses isoleucine biosynthesis in Listeria monocytogenes through a direct interaction with the ilvA transcript. Issue 10 (3rd October 2019) - Marinho, Catarina M.; Dos Santos, Patrícia T.; Kallipolitis, Birgitte H.; Johansson, Jörgen; Ignatov, Dmitriy; Guerreiro, Duarte N.; Piveteau, Pascal; O'Byrne, Conor P.
ABSTRACT: The facultative intracellular pathogen Listeria monocytogenes can persist and grow in a diverse range of environmental conditions, both outside and within its mammalian host. The alternative sigma factor Sigma B (σ B ) plays an important role in this adaptability and is critical for the transition into the host. While some of the functions of the σ B regulon in facilitating this transition are understood the role of σ B -dependent small regulatory RNAs (sRNAs) remain poorly characterized. In this study, we focused on elucidating the function of Rli47, a σ B -dependent sRNA that is highly induced in the intestine and in macrophages. Using a combination of in silico and in vivo approaches, a binding interaction was predicted with the Shine-Dalgarno region of the ilvA mRNA, which encodes threonine deaminase, an enzyme required for branched-chain amino acid biosynthesis. Both ilvA transcript levels and threonine deaminase activity were increased in a deletion mutant lacking the rli47 gene. The Δ rli47 mutant displayed a shorter growth lag in isoleucine-depleted growth media relative to the wild-type, and a similar phenotype was also observed in a mutant lacking σ B . The impact of the Δ rli47 on the global transcription profile of the cell was investigated using RNA-seq, and a significant role for Rli47 in modulating amino acid metabolism was uncovered. Taken together, the data point to a model where Rli47 is responsible for specifically repressing isoleucine biosynthesis as a way to restrict growth under harsh conditions, potentially contributing to the survival of L. monocytogenes in niches both outside and within the mammalian host.